Pengembangan Media E-Book Cerita Anak pada Pembelajaran Menulis Siswa Kelas V Sekolah Dasar - Mubarok, Ikhtiromal; Mukhlishina, Innany (EduInovasi: Journal of Basic Educational Studies, 2024)
Learning media plays a crucial role in the learning process, serving as a source of learning that helps teachers enrich students' knowledge. The objective of this research is to develop a suitable E-Book media for children's stories that can be used effectively in teaching and to describe students' responses to the media. This study adopts the Research and Development method, employing the ADDIE model. The developed media has been evaluated by subject matter experts and media experts, who deemed it "appropriate" for instructional use. This indicates that the E-Book media for children's stories meets the criteria of high quality for implementation in fifth-grade classrooms. Keywords: Learning media, Children`s stories, Indonesian.